LOCAL GOVERNMENT BUDGET ORIENTATION: A CRITIQUE OF BUDGET POLICY - MAHDALENA, MAHDALENA; ANDRY, ANDRY; HALIAH, HALIAH (Faculty of Economics and Business, Hasanuddin University, 2022)
This study aims to determine the orientation of the budget in the process of preparing and determining local government budgets. The research was conducted by the local government of Gorontalo City. Habermas’s communicative action theory approach as part of the critical approach was chosen as the method in this research to capture the reality of budget orientation in the preparation and determination of local government budgets. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The informants in this study were from BAPPEDA, members of BANGGAR, and several officials from offices related to regional finance as many as 10 people.This study finds that the act of compromise in the communication pattern of local government administration on budget policies is motivated by political interests. Budget policy decisions are dominated by the power possessed by actors to determine budget priorities. Communication practice is characterized by negotiation and compromise and ignores the value of honesty as a prerequisite for validity to fulfill comprehensive aspects of communication competence (truth, accuracy, honesty). Communication that is built only because of interest as the cause of communicative action is not effective. The results of the study show that the shackles of communication harmony are the basis for consideration for making policy changes by prioritizing rationality to gain legitimacy and trust from the public to government administrators.